(untitled) (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
This article studied the dynamics of stem growth during the three-leaf, budding, flowering and pod formanation periods of the mung bean varieties AVMU. As a result, it was found that the most positive results in the experimental system were observed in the variety AVMU 2001.